The epidemiology of traumatic brain injuries (TBI) - a literature review - S. R. Kalyan (AOSIS, 2007)
A search of the literature showed limited reported research on the epidemiology of TBI in South Africa. This prompted a search of literature on the epidemiology of TBI in the rest of the world. Traumatic brain injury (TBI) is a leading cause of death and disability in most western countries. Motor vehicle accidents (MVA) are the main cause of TBI, followed by gunshot wounds (GSW) and falls. In South Africa, road accident fatalities are 27,3 per 100 000 of the population.  The causes of death and disability vary with age, race and gender groups. Improved medical emergency care has resulted in a decrease in the mortality rate following TBI, but has increased the morbidity rate. The increase in the number of people living with neurological impairments is a significant economic burden when taking into account hospitalization, rehabilitation, medication and the loss of working hours. The emotional burden is unknown. The purpose of this paper is to place in perspective, the epidemiology of TBI, by looking at the published literature in the rest of the world.  In the developing world it is projected that the burden of disease resulting from interpersonal violence will nearly double by 2020 unless preventive action is taken. Many more people survive acts of interpersonal violence than die from them.